Solar powered water treatment device (SWAD) prototype for water quality improvement - Wan Nor Yusairah bt Wan Mohd Nasir (2023)
Lakes and ponds are complex ecosystems that demand supervising and attention to stay unpolluted. Nowadays, many of the lakes, streams, and ponds are polluted. To promote aeration in water bodies is not applicable for stagnant water because is due to its features of static stagnant water where the dynamic property of water is used. To improve water qualities and water flows of the lakes, Solar Powered Water Treatment Device (SWAD) was designed as an easy operation system and sustainability system to treat the stagnant water bodies. SWAD is designed to operate independently without being attached to other machinery. The system has been developed to study water treatment efficiency. The objectives of this study are divided into four objectives. The first objective is to design SWAD using preliminary concept design. The second objective is to simulate or model the water flow, spatial distribution of velocity and pressure on the filtering system of SWAD. To fabricate of SWAD system for water quality improvement and to determine the performance of SWAD in removing water pollutants. House of Quality (HoQ), morphological chart and pugh matrix were used to build SWAD using preliminary concept design. 3D CAD is used to design a 3D model of SWAD. Then 3D drawing was transferred into Computational Fluid Dynamic. CFD analysis is used to capture the efficiency of the SWAD by simulating and model the water flows, pressure, and velocity. After the simulation process success. The fabrication of SWAD start. The SWAD was separated into five components which are the frame, filtering system, floating device, solar panel and electric part. In the filtering system part, activated carbon was used as the treatment element due to it characteristics can apply adsorption of pollution on it. The water samples were collected at UNITEN Lake with a 103NTU turbidity value filled in 200 Gallons water tank. The water samples then being tested in the laboratory to compare the water quality as well as to measure the parameter removal such as turbidity, color, total suspended solids (TSS), Chemical Oxygen Demand (COD) and Biochemical Oxygen Demand (BOD). The removal of turbidity and color was up to 95% and 98%, meanwhile for TSS is about 96% of removal efficiency. Hence, this system is for monitoring water quality in a large aquatic area using wireless sensor networking technology.